2016
DOI: 10.1515/botcro-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of two halophytic grass species under drought stress environment

Abstract: -The physiological responses of two halophytic grass species, Halopyrum mucronatum (L.) Staph. and Cenchrus ciliaris (L.), under drought stress were evaluated. Biomass accumulation, relative water content, free proline, H 2 O 2 content, stomatal conductance, photosynthetic performance and quantum yield (F v /F m ratio) were studied. Under drought conditions, these halophytic plants expressed differential responses to water defi cit. Stomatal conductance and free proline content were higher in H. mucronatum tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…In this study, physiological and biochemical parameters used in the screening of salt or drought stress were selected (Siddiqui et al 2016) and their correlations are presented. This approach may be useful to identify physiologically tolerant genotypes of sunflower under water limited, salinity prone and combined stress environments.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, physiological and biochemical parameters used in the screening of salt or drought stress were selected (Siddiqui et al 2016) and their correlations are presented. This approach may be useful to identify physiologically tolerant genotypes of sunflower under water limited, salinity prone and combined stress environments.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant enzyme activity was higher in S. bungeana than in the other species, which indicated that S. bungeana had strong drought resistance. The Pro level was higher in A. frigida than in other species, which indicated that A. frigida was more tolerant to water stress and had higher drought resistance (Siddiqui et al, ). The drought resistance index ( D ) indicated that the drought resistance ranks of the four species in decreasing order were S. bungeana > A. frigida > H. altaicus > L. davurica , which was basically consistent with the field species distribution data in plant communities.…”
Section: Discussionmentioning
confidence: 99%
“…The Pro level was higher in A. frigida than in other species, which indicated that A. frigida was more tolerant to water stress and had higher drought resistance (Siddiqui et al, 2016 (Cai et al, 2018). At the initial stage after cropland abandonment, community coverage and transpiration were low, and soil water was relatively high, especially in the deep layer in sandy soil.…”
Section: Drought Resistance Of the Four Species And Implicationsmentioning
confidence: 93%
“…Increased CAR content may be due to protection from oxidative damage under drought stress (Filippou, Antoniou, & Fotopoulos, 2011;Man, Bao, & Han, 2011). Decline in RWC is related to cell membrane properties and its adaptability to drought stress (Chai, Jin, Merewitz, & Huang, 2010;Siddiqui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%